Fabrication of ternary and quaternary chalcogenide compounds based on Cu, Zn, Sn and Si for thin film photovoltaic applications. Issue 6 (27th February 2017) - Brammertz, Guy; Vermang, Bart; ElAnzeery, Hossam; Sahayaraj, Sylvester; Ranjbar, Samaneh; Meuris, Marc; Poortmans, Jef
Abstract : We investigated the use of ternary and quaternary chalcogenide compounds based on Cu, Zn, Sn and Si for use as high band gap absorber layers in thin film photovoltaics. We have investigated the fabrication of Cu2 Zn(Sn, Si)Se4, Cu2 Si(S, Se)3 and Cu8 Si(S, Se)6 thin film layers. Whereas, Cu2 Zn(Sn, Si)Se4 and Cu2 Si(S, Se)3 appeared to be difficult to fabricate, because the Si did not intermix well with the rest of the elements at the typical process temperatures used for glass substrates, Cu2 ZnSiSe4 and Cu8 Si(S, Se)6 could be formed. The fabricated layers were polycrystalline with a typical thickness of about 1 μm. We also fabricated solar cells with the different absorber materials, using a standard Mo back contact and CdS/ZnO buffer layer combination, but despite very bright photoluminescence response of the Cu8 SiS6 and Cu8 SiSe6 layers at an energy of about 1.84 and 1.3 eV respectively, the measured efficiencies remained below 0.1% due to particularly low photocurrents.